Rural Schools and the Digital Divide: Technology in the Learning Experience - Kormos, Erik; Wisdom, Kendra (Theory & Practice in Rural Education, 2021)
In this era of rapid technological innovation, teachers in rural public schools employ a variety of educational technology tools to facilitate student learning. However, little information is known about these teachers’ usage frequencies and perceptions of effectiveness of technology in the learning process. Furthermore, limited research exists related to the barriers rural teachers face in their adoption and use of technology. Utilizing a quantitative approach, this study investigated these perceptions among rural teachers. Findings revealed rural educators have differing opinions on usage and effectiveness of various web-based technologies and software. Teachers revealed personal trial and error as the most common way of new technology knowledge and skill acquisition. Participants reported budgetary issues as the largest barrier to technology implementation, followed by student internet access at home. Suggestions are provided so administrators and teachers can adopt and integrate appropriate educational technology tools to maximize student learning.